Penerapan Bisnis Intelijen Dalam Penyempurnaan Sistem Pada Perusahaan Ojek Online (Grab) Dengan Memanfaatkan Kelemahan Kompetitor - Anisah Anisah; Pratiwi Nila Sari; Achmad Fauzi; Geraldo Geraldo; Raihan Wicaksono; Siti Nur Assyifa; Zain Wahyu Ramadhan (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to analyze the implementation of business intelligence in refining systems at the online motorcycle taxi company Grab by leveraging competitors' weaknesses. The research method employed is qualitative with a case study approach to gain an in-depth understanding of business intelligence strategies and implementation at Grab, where data is collected from e-books, online journals, and other internet sources. The findings indicate that Grab utilizes big data and data warehouses to search for and analyze competitor data, resulting in insights that Grab can optimize their operations by analyzing operational data such as driver availability, most efficient travel routes, and wait times. Grab can also identify areas where they can enhance operational efficiency and reduce costs, as well as identify areas where they lag behind in competitiveness, expand market share, and enhance customer satisfaction. This research also presents the strategic implications of using Business Intelligence in decision-making and strategy development in transportation technology companies, thus Business Intelligence not only serves as a tool to refine systems but also as a key to winning competition in an increasingly competitive industry.